Encoding the plural-honorific suffix -ani and the imperfective anga in Malawian CiTonga (N.15) - Winfred Mkochi (LibraryPress@UF, 2019)
Many Bantu languages have the plural-honorific suffix *-Vni and the imperfective morpheme *-a(n)g-. In most of these languages, *-Vni is reported to be clearly encoded at POST-FINAL position. On the other hand, *-a(n)g- is said to be ambiguously encoded, either at EXT (extension) in one language or FV (final vowel) in another language. Still in others it coexists at both EXT and FV; there has also been a suggestion that it is encoded at POST-FINAL in several others. This article argues that the status of both the plural-honorific suffix -ani (*-Vni) and the imperfective -anga (*-a(n)g)- in CiTonga is fluid, it prevaricates between EXTENSION (suffix), FV (the commonest), and POST-FINAL (clitic). Although these formatives can be encoded at these positions, they are shown to be functionally different from extensions, inflectional vowel suffixes and clitics